Desvenlafaxine for the treatment of major depressive disorder. (July 2014) - Kornstein, Susan G; McIntyre, Roger S; Thase, Michael E; Boucher, Matthieu
<x xml:space="preserve">Abstract</x> Introduction: Major depressive disorder (MDD) is a chronic and debilitating condition often characterized by inadequate treatment. Notwithstanding the availability of more than a dozen first-line agents across disparate classes (e.g., selective serotonin reuptake inhibitors), the majority of individuals with MDD do not achieve and sustain a recovered state. A substantial percentage of MDD patients require a treatment change due to poor efficacy or tolerability. Areas covered: This review focuses on recent (≤ 5 years) literature describing the pharmacokinetics, efficacy, and tolerability of <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=desvenlafaxine&logicalOpe1=OR&field2=articletitle&text2=desvenlafaxine&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">desvenlafaxine, one of the more recently approved antidepressant drugs. Published papers identified via PubMed search and congress presentations were included. Results from short-term, placebo-controlled, MDD trials and randomized withdrawal trials, as well as post hoc analyses in patient subgroups, are reviewed. Expert opinion: Desvenlafaxine has been shown to be an effective antidepressant with a favorable safety and tolerability profile in the general MDD population and in important patient subgroups. It has several notable differences from other serotonin-norepinephrine reuptake inhibitors, and those differences suggest populations in which it may have the most clinical benefit.